2018
DOI: 10.1111/jipb.12638
|View full text |Cite
|
Sign up to set email alerts
|

KNAT7 positively regulates xylan biosynthesis by directly activating IRX9 expression in Arabidopsis

Abstract: Xylan is the major plant hemicellulosic polysaccharide in the secondary cell wall. The transcription factor KNOTTED-LIKE HOMEOBOX OF ARABIDOPSIS THALIANA 7 (KNAT7) regulates secondary cell wall biosynthesis, but its exact role in regulating xylan biosynthesis remains unclear. Using transactivation analyses, we demonstrate that KNAT7 activates the promoters of the xylan biosynthetic genes, IRREGULAR XYLEM 9 (IRX9), IRX10, IRREGULAR XYLEM 14-LIKE (IRX14L), and FRAGILE FIBER 8 (FRA8). The knat7 T-DNA insertion mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 69 publications
4
30
0
Order By: Relevance
“…The rice plants were grown in a greenhouse and cultivated as previously described (Yang et al ., ). Arabidopsis plants were grown at 22°C with 16/8 h (light/dark) photoperiod at approximately 120 μmol m −2 sec −1 light (He et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The rice plants were grown in a greenhouse and cultivated as previously described (Yang et al ., ). Arabidopsis plants were grown at 22°C with 16/8 h (light/dark) photoperiod at approximately 120 μmol m −2 sec −1 light (He et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The transcriptional repression by KNAT7 and BLH6 is enhanced by their interaction with other TFs, including OVATE FAMILY PROTEIN (OFP) 1 and 4, during SCW biosynthesis [74,75]. By analyzing different knat7 mutants, KNAT7 was shown to regulate the expression of several xylan biosynthetic genes (IRX8, IRX9, FRA8) either positively [76] or negatively [77]. This result suggests that the xylan and lignin biosynthetic pathways do not share the same regulatory network, despite their common activation by several MYB and NAC TFs [78].…”
Section: Knox Bell and Homeodomain: From Cell Division To Fiber Scwmentioning
confidence: 99%
“…Hence, KNAT7 has an unexpected role in controlling cell size. Although previous studies have proposed that the roles of KNAT7 might vary in different tissues and cell types (Li et al, 2012;He et al, 2018), its role in coordinating cell expansion and wall thickening has not yet been found in other plant species.…”
Section: Discussionmentioning
confidence: 95%
“…Although studies in several plant species have revealed that KNAT7 governs secondary wall thickening, its function differs among species. Arabidopsis KNAT7 can repress lignin biosynthesis in the interfascicular fiber cells (Brown et al, 2005;Zhong et al, 2008;Li et al, 2012) and activate xylan production in xylary tissues (He et al, 2018). The mechanism underlying KNAT7 function remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation